(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
The study was conducted in a peri-urban village named, Panchpy under Gafargaon upazila of Mymensingh district with stinging catfish (Heteropneustes fossilis ) and carps ponds to produce aquaponics vegetable kolmi (water spinach, Ipomoea aquatica ) towards using waste substances of intensive stinging catfish ponds. Aquaponic plant (water spinach, Ipomoea aquatica ) was grown in floating trays in the selected ponds. The water quality parameters including, temperature, pH, dissolved oxygen, nitrite and ammonia were measured during study period.The level of ammonia was higher in catfish pond compared to carps pond water. Inversely, the dissolved oxygen content of catfish pond water was lower than that of carps pond. In the stinging catfish pond, the mean value (± SE) of plant length, weight, number of branches and leaves were recorded at 27.67 ± 1.76, 62.67 ± 2.03, 13.00 ± 1.15 and 55.33 ± 3.18, respectively. The corresponding values 19.33 ± 1.45, 46.67 ± 1.86, 9.33 ± 1.45 and 43.00 ± 2.88, respectively in carps pond, were significantly lower than that of catfish pond. Overall the percent weight gain of kolmi was higher in catfish pond. A positive correlation was found between the length and weight of kolmi produced in both catfish and carp ponds, however R2 value of that relationship was higher for catfish pond due to higher level of available waste nutrients in water. This indicates that the potential of aquaponics research and development in intensively feed catfish aquaculture ponds at the farmer level that can feed the growing population in both rural and urban areas of Bangladesh. Res. Agric., Livest. Fish.2(1): 143-150, April 2015